Can Peripheral Skin Perfusion Be Used to Assess Organ Perfusion and Guide Resuscitation Interventions? - Bakker, Jan; Hernandez, Glenn (Frontiers in Medicine, 2020)
Although the definition of septic shock is straightforward, the physiological response to inadequate hemodynamics in patients with septic shock is variable. Therefore, the clinical recognition is limited not only by the patient’s response but also by the clinical parameters we can use at the bedside. In this short overview we will argue that the state of the peripheral perfusion can help to identify and to treat patients with septic shock.